Spectrophotometric Determination of Phenols in Aqueous Solution via Oxidative-Coupling Reaction with 4-Amino-N,N-Diethylaniline and Potassium Dichromate - M.Q. Al-Abachi; M.M. Al-Sharook; Shayma Al-Najafi (College of Education for Pure Sciences, 2005)
A simple and sensitive spectrophotornetric method for the determination ofphenol has been developed. The method is based on the oxidative-coupling reaction ofphenol with 4-amino-N,N-diethylaniline in the presence of potassium dichromate at pH 6 solution to form an intense bluish-green water-soluble dye that is stable and has a maximum absorption at 670nm. A plot of absorbance versus concentration shows that Beer's law is obeyed over the concentration range of 2.5-250 jag of phenol in a final volume of 25ml,(i-e 0.1-lOppm) with a molar absorptivity of 3.95 x 104 l.mor'cm"', a percentage recoveries of 98.10-100.75% and a relative standard deviation of better than ±0.4%, depending on the concentration level. The optimum conditions for full colour development are described and the proposed method is extended to some other phenolic compounds.